1991
DOI: 10.1159/000186302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subcutaneous and Intraperitoneal Administration of Recombinant Human Erythropoietin on Blood Pressure and Vasoactive Hormones in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: The effect of subcutaneous and intraperitoneal administration of recombinant human erythropoietin (rHuEPO) on blood pressure was evaluated in 20 patients with renal failure on continuous ambulatory peritoneal dialysis. The two groups of patients were commenced on a 16-week course of twice weekly rHuEPO by either the subcutaneous (10 patients) or the intraperitoneal route (10 patients). One patient in the latter group was subsequently excluded because of operation and transfusion. The hemoglobulin increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…In the literature, there are contrast ing data about the effects of EPO on the plasmatic levels of endothelin. Lai et al [17], e.g., did not find any action of EPO on endothelin; others, such as Tkayama [18], found an increase in the plasmatic levels of endothelin in subjects treated with therapeutic doses of rHuEPO (from 5.6 ±4.7 to 14.1 ±2.9 pg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are contrast ing data about the effects of EPO on the plasmatic levels of endothelin. Lai et al [17], e.g., did not find any action of EPO on endothelin; others, such as Tkayama [18], found an increase in the plasmatic levels of endothelin in subjects treated with therapeutic doses of rHuEPO (from 5.6 ±4.7 to 14.1 ±2.9 pg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…In humans only a very limited absorption was observed [4,12,13]. Controversial results were obtained in therapeutic studies with intraperitoneal erythropoietin [6,9,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…From this study, it seems that endothelin 1 may participate in the pathogenesis of rhuEPO-induced elevation of the blood pressure. In other studies no significant changes in plasma endothelin 1 levels were reported in patients on rhuEPO therapy [64], Summarizing, it seems that alterations in the secretion of blood pressure related hormones may be involved both in hypertensive and antihypertensive 129 mechanisms triggered by rliuEPO therapy. Controversial results observed sometimes in this respect seem to be due predominantly to a lack of standardization of conditions under which the individual hormones were assessed.…”
Section: Factors Potentially Involved In the Pathogenesis Of Rhuepo-imentioning
confidence: 79%
“…The atrial natriuretic peptide levels showed a tendency to increase at the beginning of rhuEPO therapy [63], but decreased to basal values after long-term administration of this hormone [63]. Other authors did not find similar alterations in plasma atrial natriuretic peptide levels in rhuEPO-treated patients [58,64]. It should be mentioned that short-term administration of rhuEPO to rats was accompanied by increased renin-specific mRNA in renal tissue and increased renin substrate mRNA in kidney and aorta [65], In both aorta and kidney a significant correla tion was observed between renin substrate mRNA and blood pressure [65].…”
Section: Factors Potentially Involved In the Pathogenesis Of Rhuepo-imentioning
confidence: 95%